Transparency and 'uncomfortable knowledge' in child protection. (3rd March 2016) - Bessant, Judith; Broadley, Karen
ABSTRACT: Australia's child protection systems and the provision of out-of-home care, in particular, have been subject to sustained criticism for decades from dozens of official inquiries and reviews. It is now well established that many children in state care are treated significantly less well than required by relevant legal frameworks and community standards. Much attention and significant resources have been directed toward trying to ameliorate this 'wicked problem' and yet it continues. This article focuses on one reason the problems persists, namely the secrecy and closed cultures that characterize relevant organizations which reinforce strategies of denial that avoid acknowledging or dealing with 'uncomfortable knowledge'. It is a situation many people in child protection systems confront. It is, for example, when we know abuse is taking place, or when they see or are ourselves party to corrupt or negligent practices. It is knowing that important ethical principles are being abrogated. We draw on recent official reports and inquiries noting the repeated calls for greater transparency and independent oversight. An argument is made for a default position of total transparency subject to caveats that protect privacy and any investigation underway. An account of what this can look like is offered.